(untitled) (Research, Society and Development, 2021)
Aim: To analyze the effect of Bag squeezing maneuver in heart rate variability in elderly patients admitted to an intensive care unit in the Northern Regional Hospital in the city of Sobral-CE. Method: It was an interventional study with a quantitative approach, carried out in the Intensive Care Unit of Hospital Regional Norte in the municipality of Sobral, Ceará, from January 2015 to March 2015. The research covered the elderly population hospitalized in the therapy unit intensive in the municipality of Sobral, and it performed the Bag squeezing maneuver, measuring its impact on the participants’ heart rate variability. Results: We selected 20 subjects, regardless of gender, with a mean age of 72 years, with the most frequent pathogenic pneumonia, which showed a decrease in vital signs after the effect of the maneuver during the search. Regarding maneuver does not influence significantly the autonomic modulation, we can see a reduction of RR complex during operation and maintenance for an extended time. However, this is not noticeable in SDNN index during the maneuver, featuring a minor change in heart rate variability. Conclusion: We conclude that the Bag squeezing maneuver is a technique that does not cause repercussions on heart rate variability and has a significant effect on oxygen saturation, reduction of heart and respiratory rates, besides blood pressure.